Floss abrasion: a cautionary tale - Cooper, J. (Eur Arch Paediatr Dent, 2020)
BACKGROUND: The Hall technique for placement of preformed metal crowns is widely used in the UK for the management of decayed primary molar teeth. The creation of space is achieved by the placement of orthodontic separators adjacent to the tooth requiring restoration. Highlighting the first reported case of an abrasion caused by dental floss, this communication describes the clinical findings of an 8-year-old patient following placement of orthodontic separators. CASE REPORT: An 8-year old boy attended the University Dental Hospital of Manchester for placement of orthodontic separators prior to restoration URE, ULE, LLE, and LRE with preformed metal crowns using the hall technique. The following week he presented with a 2cm abrasion to his right cheek, which had been caused by dental floss used in placement of the orthodontic separators. FOLLOW UP: Conservative advice was given and the lesion had resolved completely at a 2-week review. CONCLUSION: This case is a timely reminder of the importance of adequate lip retraction and soft tissue management during placement of orthodontic separators.